Critical Business? Critical Management Studies (CMS) perspectives on Corporate Social Responsibility (CSR) - Wallis, Matthew (2009)
Critical Management Studies (CMS) and Corporate Social Responsibility (CSR) are two theoretical traditions within the business school that are among the most critical of corporate management practices. While both are very distinct traditions, I argue that they have what amounts to certain shared goals to radically rethink and re-shape business and its “accepted utilitarian justification of business in terms of economic growth and material accumulation” (Crane 2000 p.674). One of the primary aims of this dissertation is to prove that the goals of CMS and CSR are proximate by detailing and defining both. Once this detailing of CSR and CMS is completed in Chapters 2 and 3, I shall question why there is little dialogue between these traditions, especially considering this when certain distilled characteristics of each tradition are viewed side by side in chapter 4. I shall then investigate the reasons for this gap in chapter 5. Additional aims in this dissertation include investigating and evaluating the differences in the CMS and CSR approaches to business, the corporation and management and the role these play in the world as currently configured. This dissertation presents the argument that in each tradition the role of business and particularly the assumptions about business can be categorised, evaluated and compared to each other despite both CMS and CSR being “essentially contested terms” (Moon, Matten & Crane 2005 p.434).